AAV-mediated IL-10 gene transfer counteracts inflammation in the hypothalamic arcuate nucleus and obesity induced by high-fat diet. (April 2017) - Nakata, Masanori; Yamamoto, Sawako; Okada, Takashi; Yada, Toshihiko
Abstract: Consumption of high-fat diet (HFD) induces energy imbalance and consequently obesity. In the pathogenesis of obesity, HFD triggers inflammation in the hypothalamus including arcuate nucleus (ARC). Interleukin-10 (IL-10) is a representative anti-inflammatory cytokine, known to ameliorate the adipose tissue inflammation and insulin resistance in obesity. However, the effect of IL-10 on the hypothalamic inflammation remains less defined. We here report the effect of over-expression of murine IL-10 using adeno-associated virus (AAV) vector on the inflammation in ARC and feeding behavior in HFD-induced obese (DIO) mice. DIO mice exhibited reduced POMC expression and elevated IKKs (IκB kinases) and SOCS3 expression in ARC. Overexpression of mIL-10 using AAV vector ameliorated obesity in parallel with restoration of ARC POMC expression in DIO mice. Moreover, IL-10 treatment suppressed IKKs activation and SOCS3 expression in ARC of DIO mice. These results suggest that IL-10 gene transfer provides an effective approach for counteracting HFD-induced inflammation and leptin resistance in ARC to prevent progression of obesity. Highlights: AAV-mediated IL-10 gene transfer ameliorates obesity and hyperphagia in DIO mice. IL-10 gene transfer ameliorates impaired POMC expression and leptin resistance in DIO mice. IL-10 gene transfer ameliorates inflammatory IKK hyperactivity in hypothalamic ARC in DIO mice.